Development of mental health first-aid guidelines for depression: a Delphi expert consensus study in Argentina and Chile - Encina Zúñiga, Esteban (2023)
Background: Depression is one of the most common mental health problems worldwide and, while prevalence rates in Latin America are relatively high, most people who meet the criteria for diagnosis do not receive treatment. Family and friends of a person with depression can play an important role in supporting a person to seek and engage with treatment. However, many people do not have the necessary skills or confidence to help. English-language mental health first aid guidelines have been developed to support people to provide such help. The aim of this study was to culturally adapt these guidelines for Chile and Argentina. Methods: A Delphi expert consensus study was conducted with two expert panels, one of people with lived experience of depression (either their own or as a carer; n = 26) and one of health professionals (n = 29). Overall, 172 statements from the English-language guidelines were translated and compiled into a questionnaire. Participants were asked to rate statements based on how essential or important those statements were for Chile and Argentina and to suggest new statements if necessary. Results: Data were obtained over two survey rounds. Consensus was achieved on 172 statements. A total of 137 statements were adopted from the English-language guidelines, whereas 35 new endorsed statements were generated from panel suggestions. There were similarities between the English-language guidelines and those for Chile and Argentina. The adapted guidelines did not include some of the items from the English-language guidelines related to commenting on a person’s strengths or making judgements about their character, and also incorporated new items related to the incorporation of sociocultural considerations as causes of depression and attention to inequities in mental health. Conclusions: The significant number of new items underscores the importance of undertaking a careful process of cultural adaptation. Further research on dissemination and incorporation of the guidelines into the Mental Health First Aid training course for Chile and Argentina is still required.